A 14-Week Intervention Study on Changing Preservice Teachers’ Psychological Perspectives on Inclusion: Explicit and Implicit Attitudes, Self-Efficacy, and Stress Perception Toward Inclusion - Lautenbach, Franziska; Korte, Johanna; Möhwald, Aiko; Heyder, Anke; Grimminger-Seidensticker, Elke (Frontiers in Education, 2020)
Research has indicated the importance of preservice teacher education programs that focus on fostering positive psychological aspects relevant to teaching in inclusive settings, such as attitudes or self-efficacy. Previous research lacks theoretical underpinning and is limited because of methodological characteristics of the studies (e.g., no control group). Thus, in a quasi-experimental design the current study aimed to investigate the effects of theoretically derived interventions (IG1: information-based cognitive intervention group; IG2: information-based and practical field experience intervention group) in comparison to a control group (CG) on changes in preservice teachers’ perspective on teaching inclusively, i.e. explicit and implicit attitudes, self-efficacy, and stress perception, all relevant to teach in inclusive settings. Results of four separated repeated-measure analysis of variances, with time of assessment (before vs. after) as a within-subject factor and group (CG, IG1, and IG2) as a between-subject factor, showed no differences in the development (pre- to post-intervention) between CG and IG1 as well as CG and IG2 in any of the dependent variables. However, significant differences in changes in explicit attitudes and stress perception were found between IG1 and IG2 in favor of IG2. Results will be discussed considering confounding variables that future research should further investigate.